Leader’s Efforts in Providing Staff Needs in Pita Kuning Anak Indonesia Foundation - Cindy Aulia; Sari Viciawati Machdum (Cita Konsultindo Research Center, 2024)
The purpose of this writing is to discuss the Leader's efforts in providing staff needs andstaff’s efforts to give best service for clients. Using a qualitative approach withdescriptive research, the researcher conducted research including observation,interview and literature study techniques and used research supporting instruments,namely interview guides, voice recorders and cameras. The approach in HumanServices Organizations that underlies this research is a human relations approach whichexplains the relationship between management, front line staff, and clients, whichultimately is the best service for clients. The conclusion of this research is that Leaderhas efforts to provide staff needs at the Pita Kuning Anak Indonesia Foundation withvarious policies and activities, which are based on analysis using Maslow's hierarchy ofneeds theory and employee working needs, Leader have attempted to provide needsthrough fulfilling physiological needs to self-actualization. Staff are also able to give thebest service for clients through efforts, such as providing services according to needs,obtaining appropriate resources. needed, utilizing technology, and forming a team thatsupports each other.Key: Leader, Staff Needs, Human Relations Approach, Human ServicesOrganization